Estratégias de enfrentamento em jogadores de futebol - Verardi, Carlos Eduardo Lopes [UNESP] (2011)
The aim of this study was to identify scores of interest related to coping strategies used by professional and amateur football players. Participants were 134 male football players, 71 professionals (age=22,77±3,98 years) and 63 amateurs (age=17,18±0,84) from three teams participating on the First Division State Championship). The players answered individually to the Coping with Problems Scale. Significance level was P<0.05. When coping strategies were compared based on game position and player category (professional or amateur), lateral player amateurs used more wishful thinking /religious practices (P=0.042) than professionals. Coping Focused Problem was the most used strategy used by both the professionals and amateurs, except the amateur laterais, who used more wishful thinking /religious practices.